A mysterious case of an elevated dome of the right diaphragm. Issue 2 (June 2020) - Gothi, Dipti; Patro, Mahismita; Agarwal, Mohit; Vaidya, Sameer
A 63-year-old, nonsmoking man presented with dry cough and fever of 2 days' duration. On enquiry, he also complained of dyspnoea on exertion of modified Medical Research Council grade 1 for 2 months. There were no other respiratory complaints. He was diagnosed with a progressive supranuclear palsy-type parkinsonian disorder 2 years ago. He was taking levodopa (100 mg) plus carbidopa (25 mg) thrice daily for that condition. There was no significant occupational history, family history or similar illness in the past. He was conscious and oriented with a pulse of 84 per min, blood pressure of 124/76 mmHg, respiratory rate of 16 per min and oxygen saturation of 96%. A respiratory system examination revealed dull notes and reduced breath sounds in the right basal region. Upon neurological examination, he had a mask-like face and speech abnormality. Combined collapse of the right middle lobe and lower lobe requires CT scan for confirmation. Excessive dynamic airway collapse (EDAC) can cause lobar collapse. Surgical intervention is required in EDAC only in symptomatic patients with >95% collapse. https://bit.ly/2UXTuw7